PELATIHAN MOTIVATIONAL DAN INSTRUCTIONAL SELF-TALK UNTUK ATLET POMNAS CABANG OLAHRAGA TENNIS LAPANGAN SULAWESI SELATAN - Muflih Wahid Hamid; Faradillah Firdaus; Muhammad Rhesa; Arfandi Akkase; Muhammad Sadzali (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
Self-talk has been widely known and used as a psychology technique in sports. It is a fundamental technique that can lift the spirit of players up if it is done sufficiently. Apart from that, self-talk is also able to improve athletes' technical skills if it is executed well. This community service targets the use of self-talk in POMNAS tennis athletes who will compete at POMNAS 2023 next November. This community service uses a training and psychoeducation approach, where athletes will be given material related to mental skills of motivational self-talk and instructional self-talk. The results of this training and psychoeducation show an increase in athletes' knowledge regarding self-talk and how to use it appropriately. The hope is that this training and psychoeducation will be able to help athletes to provide their best abilities during the implementation of POMNAS 2023 in Banjarmasin.